ACUTE-PHASE REACTIONS, INCLUDING CYTOKINES, IN PATIENTS BITTEN BY BOTHROPS AND CROTALUS SNAKES IN BRAZIL - Barraviera, B. [UNESP]; Lomonte, B.; Tarkowski, A.; Hanson, L. Å.; Meira, D.a. [UNESP] (Centro de Estudos de Venenos e Animais Peçonhentos - CEVAP, Universidade Estadual Paulista - UNESP, 1995)
Thirty-one patients bitten by venomous snakes in Botucatu area (State of São Paulo - Brazil), sixteen by Bothrops spp. and fifteen by Crotalus durissus terrificus, were studied. The group comprised twenty-nine males and two females, ranging from fourteen to sixty-three years of age (mean 33 ± 15). Leukocytosis with neutrophilia and lymphopenia, increase of mucoproteins and C-reactive protein, decrease of total serum protein and albumin, were observed on the first day after the accident. In addition, increased serum levels of the cytokines IL-6 and IL-8, but not of IL-1b and TNF-a, were observed. The alterations were generally more intense in patients bitten by Crotalus durissus terrificus than by Bothrops spp. It is concluded that these snakebite envenomations closely resemble an acute trauma, inducing a typical acute-phase response.
Keywords: snake venom; acute-phase reactions; cytokines; C-reactive protein; inflammation